Pembuatan Bioetanol Dari Nira Aren Menggunakan Proses Fermentasi Dengan Variasi Kecepatan Pengadukan Dan Waktu Fermentasi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Bioethanol is a liquid sugar fermentation process results from a source of carbohydrate (starch) using microorganisms. Bioethanol is an alternative raw materials are cheap and environmentally friendly. One of the raw materials for bioethanol production is a palm juice. Aren is one of the most bioethanol feedstock and productive potential as well as a fairly high sugar content. Stirring speed is an important aspect which affects the quality of mixing in stirred tank. Fermentation time very big influence on the activity of yeast because the longer the fermentation, the more the number of increasingly active yeast or yeast to proliferate. The purpose of research to get the operating conditions for bioethanol production from palm juice on the highest level (%) with stirring speed and time variation of fermentation. Through the process of fermentation using yeast Saccharomyces cereviceae, glucose is converted into ethanol and carbon dioxide. Preparation starter made with yeast inoculum process Saccharomyces cereviceae at 10% of yeast fermentation medium so adaptable and ready for fermentation. Fermentation takes place in batches with a volume is 2 liters of fermentation medium, stirring speed variation 200, 250, 300 and 350 rpm and fermentation time variation of 24, 48, 72 and 96 hours. Ethanol concentration was analyzed by using alcohol meters. The optimum fermentation process is shown in the stirring speed of 350 rpm fermentation time-72 hours with yield obtained 82,53% and ethanol concentrations obtained 7% (v / v) or 55,25 mg / ml.Keywords: Aren, Bioethanol, Palm Sugar, Saccharomyces cerevisiae, Stirring Speed